2008
DOI: 10.1111/j.1348-0421.2008.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interferon‐α production and impaired regulatory function of plasmacytoid dendritic cells induced by the hepatitis C virus NS 5 protein

Abstract: pDC are known to produce large amount of IFN-α/β in response to viruses, and act as a major link between the innate and adaptive immune response. This study concentrated on the interaction of human peripheral blood derived pDC with HCV NS3, NS4, and NS5 proteins, and their maturation, cytokine secretion and functional properties. It was shown that HCV NS5 interferes with CD40L induced maturation of pDC as indicated by decreased expression of CD83 and CD86 markers. CpG ODN stimulated HCV NS3 and NS5 treated pDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Recent studies have shown that another non-structural HCV protein, NS5A, interacts with the TLR7 and TLR9 adaptor MyD88 to prevent recruitment of IRAK1 and assembly of a multiprotein signal-transducing complex [48,49]. However, this interaction also does not seem to occur in pDCs in which HCV does not replicate and thus non-structural HCV proteins are not expressed [44].…”
Section: Reviewmentioning
confidence: 88%
“…Recent studies have shown that another non-structural HCV protein, NS5A, interacts with the TLR7 and TLR9 adaptor MyD88 to prevent recruitment of IRAK1 and assembly of a multiprotein signal-transducing complex [48,49]. However, this interaction also does not seem to occur in pDCs in which HCV does not replicate and thus non-structural HCV proteins are not expressed [44].…”
Section: Reviewmentioning
confidence: 88%
“…Alternatively, the E1 protein (which was not tested in this study) could play a role in mediating the inhibition to CpG-A induced production of IFN-α. A recent report by Amjad et al [46] showed that non-structural proteins of HCV (namely NS3 and NS5) inhibit TLR9-induced IFN-α secretion. Because HCV particles do not contain non-structural proteins and because HCV does not express its genome in pDCs [21], it is difficult to interpret these results in the context of interaction of NS3 and NS5 with circulating pDCs studied in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies reported that DCs obtained from chronically-infected patients were phenotypically immature and failed to upregulate maturation (costimulatory) markers in response to stimuli such as TNF-α 66 , 73 . Circulating pDCs in chronic HCV-infected patients exhibit: diminished HLA-DR expression, a markedly reduced capacity to secrete IFN-α and, consequently, decreased anti-viral potency 36 , 39 , 44 , 67 , 68 , 80 . mDCs in chronic HCV infections secrete significantly lower levels of IL-12 and increased concentrations of IL-10, which tends to skew the immune response toward tolerance and a reduced ability to induce T-cell proliferation and T h1 polarization 36 , 47 , 49 , 67 , 69 , 72 , 75 - 77 , 81 .…”
Section: Contribution Of Dcs To the Pathogenesis Of Hepatitis Cmentioning
confidence: 99%